Pengaruh Model Inkuiri Terbimbing Terhadap Hasil Belajar Fisika Siswa SMA - Kamaluddin; Edi Firmansyah; Swandi (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to determine the extent of the influence of the guided inquiry model on high school students' physics learning outcomes. This research is a quasi-experimental research with a nonequivalent control-group design. The population of this study was all students of class X MIA at SMAN 2 Dompu. The class that was used as a place of research was class X MIA1 as the control class and class X MIA2 as the experimental class. Data collection using the multiple-choice test. Multiple-choice tests are used to measure student learning outcomes. The hypothesis test used is the t-test (independent t-test). The results showed that learning with the Guided Inquiry model had a positive effect on student learning outcomes based on the results of a significance value less than 0.05 (0.000 < 0.05). The results of the statistical analysis explained that the experimental class students' learning outcomes were significantly better than the control class. The results showed that the Guided Inquiry model had a more positive effect than the conventional model on high school students' learning outcomes.